Teacher perception on the potential of flipped classroom pedagogical practice in enhancing classroom interactions in Singapore primary classrooms. (2nd July 2020) - Abdul Kader, Hajera Bibi
ABSTRACT: In many Singapore schools, there are large class sizes comprising about thirty to forty students in each class. In such large classes, the opportunities for interactions between teachers and their students and among students can be limited, especially when teacher-centred, didactic teaching practices are adopted. This small-scale research project explored the potential of a flipped classroom pedagogical practice in one Singapore primary school on how it can contribute to primary level classroom interactions. Through interviews with teachers who had implemented flipped classrooms, the practice was explored if it has the potential to contribute towards classroom interactions.